What is the feasibility of switching to 200IU OnabotulinumtoxinA in patients with detrusor overactivity who have previously received 300IU? - Malki, Manar (Polish Urological Association, 2014)
INTRODUCTION: To assess the feasibility of converting from 300IU to 200IU OnabotulinumtoxinA in patients diagnosed with either idiopathic detrusor overactivity (IDO) or neurogenic detrusor overactivity (NDO). MATERIAL AND METHODS: Retrospective case–notes review of patients who were converted from 300IU to 200IU OnabotulinumtoxinA. Subjective patient reported improvements at interview and bladder diary reported parameters of urgency, urgency incontinence, frequency and nocturia. RESULTS: Forty–four patients had received 300IU OnabotulinumtoxinA and were switched to 200IU after July 2008, 28 for IDO and 16 for NDO. Thirty–seven patients reported ongoing improvement with 200IU OnabotulinumtoxinA, six patients had worsening in their symptoms since down–titrating to 200IU and one patient did not attend follow–up. Improvement in urgency and urgency incontinence episodes per day were 82% and 72%, respectively, in patients who received 200IU. Of the 44 patients, 39 continued to receive 200IU, four requested up–titration to 300IU (due to decreased effect) and one did not attend after the 1st treatment. After converting from 300IU to 200IU, additional three patients were started on CISC for de novo voiding difficulty. CONCLUSIONS: Seventy–nine percent of patients were satisfied with their symptoms after switching from 300IU to 200IU OnabotulinumtoxinA. Only 9% of patients (all with NDO) reverted back to receiving 300IU. This study showed similar efficacy and longevity in the majority of patients (90%) using 200IU in both NDO and IDO.